2008
DOI: 10.1016/j.bone.2008.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of risedronate on hip structural geometry: A 1-year, double-blind trial in chemotherapy-induced postmenopausal women

Abstract: Introduction-Chemotherapy induced menopause is associated with bone loss. The effect on structural geometry is unknown. Our objective was to determine if oral bisphosphonate therapy could maintain or improve femoral geometry in breast cancer patients with chemotherapy-induced menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Improvements in bone geometric properties have also been reported in women receiving therapy with alendronate [27][28][29] or risedronate [29,30] vs. placebo. Additionally, benefits to hip structural geometry have been observed with non-bisphosphonate osteoporosis treatment options, including raloxifene [31], teriparatide [32][33][34], and denosumab [35].…”
Section: Discussionmentioning
confidence: 92%
“…Improvements in bone geometric properties have also been reported in women receiving therapy with alendronate [27][28][29] or risedronate [29,30] vs. placebo. Additionally, benefits to hip structural geometry have been observed with non-bisphosphonate osteoporosis treatment options, including raloxifene [31], teriparatide [32][33][34], and denosumab [35].…”
Section: Discussionmentioning
confidence: 92%
“…Combination therapy resulted in significantly greater improvements in CSA and estimated CT at the narrow neck and in all parameters at the intertrochanter when compared with hormone monotherapy, but only in CSA and SM at the narrow neck when compared with alendronate monotherapy. In a 1-year study of 81 women with chemotherapy-induced ovarian failure, no significant differences were seen at the narrow neck in any HSAderived geometric parameter in women receiving 35 mg of risedronate weekly compared with placebo [33]. Significant differences compared with placebo were seen at the intertrochanteric and shaft ROIs in the CSA and BR, but not in the SM.…”
Section: Discussionmentioning
confidence: 95%
“…Uusi-Rasi et al reported the greatest improvement at the narrow neck with teriparatide treatment [19]. We previously reported the greatest impact of risedronate at the intertrochanteric site, which is composed of more trabecular than cortical bone [20]. The impact of treatment on the ratio of trabecular versus cortical bone may be responsible for some of these differences in site-specific findings.…”
Section: Discussionmentioning
confidence: 99%
“…The HSA methodology has several limitations [11, 20, 22]. Hip structural analysis is obtained indirectly by mathematical manipulation of two-dimensional data generated by DXA scanners.…”
Section: Discussionmentioning
confidence: 99%